1999
DOI: 10.1071/aj98003
|View full text |Cite
|
Sign up to set email alerts
|

MARGIN-SCALE, BASEMENT-INVOLVED COMPARTMENTALISATION OF AUSTRALIA'S NORTH WEST SHELF: A PRIMARY CONTROL ON BASIN-SCALE RIFT, DEPOSITION AL AND REACTIVATION HISTORIES

Abstract: Australia's North West Shelf is segmented into four discrete margin-scale compartments which have distinct rift and reactivation histories. Two of the margin segments, the Carnarvon and Bonaparte compartments, are very wide (500–600 km), marginal plateau systems, whereas the other two segments, the Canning and Browse compartments, are narrower and steeper. The boundaries between individual rift compartments appear to be controlled by Proterozoic fracture systems.The Browse-Bonaparte transition zone is a major,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…2): the Timor and the Browse compartments (O'Brien et al, 1996b(O'Brien et al, , 1999. The boundary zone between these two compartments is a fundamental, north-west trending Proterozoic lineament or fracture system, which has acted as a long-lived fault relay zone.…”
Section: Regional Geology Of Study Areamentioning
confidence: 99%
“…2): the Timor and the Browse compartments (O'Brien et al, 1996b(O'Brien et al, , 1999. The boundary zone between these two compartments is a fundamental, north-west trending Proterozoic lineament or fracture system, which has acted as a long-lived fault relay zone.…”
Section: Regional Geology Of Study Areamentioning
confidence: 99%
“…Table 1 Literature that present data for Quaternary tectonic deformation the Carnarvon Basin. Raggatt (1936), Clarke (1938), Teichert (1948), Condon et al (1955), Condon et al (1956), McWhae et al (1956), Boutakoff (1963), Raynor and Condon (1964), Baxter (1967), Wyatt (1967), Hancock (1969), Allen (1972b), van de Graaff et al (1976), Denman and van de Graaff (1977), Veeh et al (1979), Megallaa (1980), Hocking (1985), Hocking et al (1987), Hocking (1988), Malcolm et al (1991), Kendrick et al (1991), Wyrwoll et al (1993), Baillie and Jacobson (1995), Crostella (1995), Logan (1987), Crostella and Iasky (1997), Keep et al (1998), O'Brien et al (1999, Keep et al (2000), Ellis and Jonasson (2001), Hearty et al (2002), Keep et al (2002), Longley et al (2002), Cathro and Karner (2006), Clark (2006), Keep et al (2007), Hillis et al (2008), Revets et al (2009) Although there are two contrasting views presented in the literature, it is misleading to characterize the opposing views as comparable in terms of their breadth and volume of research. We have found only two published papers that specifically interpret data from the Cape Region as indicating tectonic stab...…”
Section: Introductionmentioning
confidence: 96%
“…1) reflects the pre-collisional geometry of the Bonaparte Basin has also been proposed (O'Brien et al, 1999;Keep et al, 2003;Fig. 10;Harrowfield and Keep, 2005), and is generally accepted from both stress and strain data (O'Brien et al, 1999;Hillis et al, 1997;Hillis and Reynolds, 2000;Harrowfield et al, 2003;Harrowfield and Keep, 2005). Furthermore, various workers have previously suggested that an outlier of Australian continental crust collided with the subduction zone at some point prior to the main collision (e.g., Richardson and Blundell, 1996;Keep et al, 2003;.…”
Section: Sse Nnwmentioning
confidence: 86%
“…15), and became incorporated into the orogenic wedge generated by the collision. Similarities between the inherited rift architecture of the Carnarvon and Bonaparte basins have been previously recognised (O'Brien et al, 1999;Harrowfield et al, 2003;Harrowfield and Keep, 2005), especially in terms of their upper-plate/lower-plate extensional geometries (Lister et al, 1986;O'Brien et al, 1999). That the Carnarvon Basin (Fig.…”
Section: Sse Nnwmentioning
confidence: 92%
See 1 more Smart Citation